F. VON HAYEK’S THEORY OF SPONTANEOUS ORDER - О. Nesterenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The essence and the genesis of spontaneous order are disclosed in the context of critical analysis of constructivism. The author’s approach to the definition of the characteristic features of the spontaneous order is proposed. The dichotomy of the order is revealed towards the economic sphere in form of spontaneous order and organization.